2018
DOI: 10.1111/jce.13436
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotic envelopes to prevent cardiac implantable electronic device infections: A meta‐analysis

Abstract: The use of antibiotic envelopes in CIED implant is associated with a significantly lower rate of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
(44 reference statements)
0
24
0
2
Order By: Relevance
“…Strategies to minimize the risk of CDIs include local antisepsis during implantation or the use of commercially available antibacterial envelopes (TYRX Absorbable Antibacterial Envelope, Medtronic Inc., Mounds View, MN, USA), the latter of which have been demonstrated to reduce the CDI rate in multiple studies. 6,[22][23][24][25][26][27] Two recent contributions to the literature now provide a consensus on the prevention of infections in CIED patients, as well as a survey of different practice across the world. 28,29 One large randomized controlled trial (PADIT) 30 was recently completed comparing the standard pre-operative systemic IV antibiotic dosing regimen to an incremental systemic antibiotic dosing regimen that included an additional pre-operative IV antibiotic, a perioperative antibiotic pocket wash, and post-operative antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to minimize the risk of CDIs include local antisepsis during implantation or the use of commercially available antibacterial envelopes (TYRX Absorbable Antibacterial Envelope, Medtronic Inc., Mounds View, MN, USA), the latter of which have been demonstrated to reduce the CDI rate in multiple studies. 6,[22][23][24][25][26][27] Two recent contributions to the literature now provide a consensus on the prevention of infections in CIED patients, as well as a survey of different practice across the world. 28,29 One large randomized controlled trial (PADIT) 30 was recently completed comparing the standard pre-operative systemic IV antibiotic dosing regimen to an incremental systemic antibiotic dosing regimen that included an additional pre-operative IV antibiotic, a perioperative antibiotic pocket wash, and post-operative antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship was demonstrated by a clinical study of sternal wound infection, which reported that treatment of wound infection using a collagen implant impregnated with gentamicin was effective, even when antibiotic‐resistant S. epidermidis was present, presumably due to high local concentrations of gentamicin 36 . Indeed, the clinical efficacy of local delivery of gentamicin for prevention of surgical site infection has been demonstrated across multiple indications, including cardiac, orthopedic, and gastrointestinal procedures, without risk of systemic exposure 28,29,37–40 . The very high local gentamicin concentrations achieved in this study suggest that bacterial killing should occur rapidly for key bacterial species.…”
Section: Discussionmentioning
confidence: 62%
“…Earlier studies have demonstrated reduced infection rates with local application of gentamicin containing collagen sponge during CIED implantation. 28,29 Furthermore, Deering et al 30 demonstrated that after hydration of ECM envelope in different antibiotics solution, elution was observed for a period of up to 6 days. In this same study, subsequent experiments performed using an animal model of cardiac device pocket infection showed that the released antibiotics (vancomycin or gentamicin) substantially reduced colonization by two strains of Staphylococcus on CIED devices.…”
Section: F I G U R E 1 Extracellular Matrix Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…Gleiches gilt für antibiotikahaltige Wundspülungen, die in dieser Arbeit sogar einen Trend zu vermehrten Wundinfektionen aufwiesen. Auch die in anderen Untersuchungen durchaus positiv bewerteten antibakteriell beschichteten Netze [1,2] zeigten hier keinen protektiven Effekt, so dass ihr Einsatz im Alltag derzeit auf Reimplantationen, insbesondere bei Austausch des Fremdmaterials aufgrund einer Infektion, beschränkt werden sollte [3].…”
unclassified